2001
DOI: 10.1103/physrevstab.4.104401
|View full text |Cite
|
Sign up to set email alerts
|

Guiding-center Vlasov-Maxwell description of intense beam propagation through a periodic focusing field

Abstract: This paper provides a systematic derivation of a guiding-center kinetic model that describes intense beam propagation through a periodic focusing lattice with axial periodicity length S, valid for sufficiently small phase advance (say, s , 60 ± ). The analysis assumes a thin ͑a, b ø S͒ axially continuous beam, or very long charge bunch, propagating in the z direction through a periodic focusing lattice with transverse focusing coefficients k x ͑s 1 S͒ k x ͑s͒ and k y ͑s 1 S͒ k y ͑s͒, where S const is the latti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…These units are identical to those used in Ref. 28 where is shown that for thermal equilibrium distributions, a beam under constant focusing is specified by a single dimensionless parameter. In the present system of units, this dimensionless parameter is given by…”
Section: Calculations Of Distributions With Purely Linear Focusingmentioning
confidence: 97%
See 1 more Smart Citation
“…These units are identical to those used in Ref. 28 where is shown that for thermal equilibrium distributions, a beam under constant focusing is specified by a single dimensionless parameter. In the present system of units, this dimensionless parameter is given by…”
Section: Calculations Of Distributions With Purely Linear Focusingmentioning
confidence: 97%
“…23,28,29 The averaged Hamiltonian allows one to look for more realistic distribution functions that are close but not exactly at equilibrium. These methods were developed primarily for application to linear focusing systems.…”
mentioning
confidence: 99%
“…Such a distribution, due to its highly inverted population in phase space, of course is of very limited practical interest. While Hamiltonian averaging techniques have been developed [31][32][33][34] that justify the smooth-focusing approximation and thereby permit investigation of a whole class of (approximate) beam equilibria, these averaging techniques typically require sufficiently small vacuum phase advance (s vac , 60 ± , say) and other approximations for their validity. Therefore, whether or not there exist periodically focused non-KV solutions to the Vlasov-Maxwell equations remains a question of continued fundamental importance, which we examine in this paper for an intense sheet beam propagating through a periodic focusing field.…”
Section: Introductionmentioning
confidence: 99%
“…(37) provides a convenient unit in which to measure the growth rate of the Weibel instability in the subsequent numerical analysis of the general dispersion relation (26). In the subsequent analysis of the dispersion relations (26) and (29), it is useful to define …”
Section: Weibel Instability For Step-function Density Profilesmentioning
confidence: 99%